2013
DOI: 10.1002/jmv.23455
|View full text |Cite
|
Sign up to set email alerts
|

Association of the CT values of real‐time PCR of viral upper respiratory tract infection with clinical severity, Kenya

Abstract: Quantitative real-time polymerase chain reaction (qRT-PCR) assay of the upper respiratory tract is used increasingly to diagnose lower respiratory tract infections. The cycle threshold (CT ) values of qRT-PCR are continuous, semi-quantitative measurements of viral load, although interpretation of diagnostic qRT-PCR results are often categorized as positive, indeterminate, or negative, obscuring potentially useful clinical interpretation of CT values. From 2008 to 2010, naso/oropharyngeal swabs were collected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 44 publications
5
76
1
3
Order By: Relevance
“…In the latter study, sample quality was not measured and therefore could not be corrected by RNase P copy number. Additionally, samples were collected from hospitalized infants only and later into the course of infection compared to the current study [17] Others have reported similar associations between viral load and disease severity, but the associations are weak and come either from hospitalized infants [2023] or infants healthy enough to stay home [19, 24]–rarely both [26]. Additionally, most of the samples were collected later in the course of infection than those analyzed here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the latter study, sample quality was not measured and therefore could not be corrected by RNase P copy number. Additionally, samples were collected from hospitalized infants only and later into the course of infection compared to the current study [17] Others have reported similar associations between viral load and disease severity, but the associations are weak and come either from hospitalized infants [2023] or infants healthy enough to stay home [19, 24]–rarely both [26]. Additionally, most of the samples were collected later in the course of infection than those analyzed here.…”
Section: Discussionmentioning
confidence: 99%
“…Results comparisons are confounded by differences in study design and measurement methods. Most samples have been collected late in infection from hospitalized children [2023, 25] or from children healthy enough to stay home [19, 24]; and most lack measurements of host response [1922, 26]. Thus, there is a systematic lack of viral load and host response data, especially from time points early in the course of illness, from young children ultimately experiencing a broad range of disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of multiple-viral infections in one single patient is reported as high as 14 -44%, depending on different populations and test panels 66 . In a multicentre study, involving 2207 children less than two years of age, the incidence of multiple infections in children hospitalized for bronchiolitis was 30 percent 67 .…”
Section: Multiple-viral Infectionsmentioning
confidence: 99%
“…Sommige onderzoekers suggereren een positieve relatie hiertussen [63][64][65][66][67][68][69][70][71][72] , terwijl anderen die relatie niet zien [73][74][75][76][77][78] In de kindergeneeskunde praktijk is virale diagnostiek vaak gebruikt als een enkelvoudige meting bij eerste presentatie van een kind op de spoedeisende hulpafdeling of polikliniek. Deze omstandigheden zijn echter niet optimaal om de relatie tussen viral load en ziekte-ernst te bestuderen, omdat viral load een dynamisch proces is.…”
Section: Viral Loadunclassified
“…Several laboratory techniques have been used in the diagnosis of HHRSV and among than Real-Time polymerase chain reaction (qPCR) can be used not only to detect the virus, but also to quantify them and try to do a parallel with the severity of HHRSV infection [7].…”
Section: Introductionmentioning
confidence: 99%